FAKTOR PENYEBAB PERCERAIAN SUAMI ISTRI (Studi Kasus di Kenagarian Kapuh Utara Kecamatan Koto XI Tarusan) - Desrianti, Lusi; Arief, Asmaiwaty; Gusneli, Gusneli (Bimbingan dan Konseling, 2014)
The backgroud of this research is about high level of breakup at Kenagarian Kapuh Utara Kecamatan Koto XI Tarusan that is caused least understanding husband and wife are about meaning of marriage, leaving their partner because they do not have children, material needs does not suffice, least communication among them, happening action of physical hardness. The kinds of this research is Qualitative Research which is study case. In this research is source of main data research that is chosen based procedure of Snowball is husband and wife is breakup amount 4 couple. The data collection of the research is toward observation, interview and documentation. The result of this research say that 1). Cause factors breakup thai are seen from phisiology of couple such as: a) Money income is too low, b) Often happen hardness home, c) Husband ignores their obligation at home and arranges children, d) The couple does not have children since life home. 2). Cause factors breakup which are looked from physicology condition alike: a) Does not appreciate partner, b) Often jealous and suspicious, c) Least communication, d) accepting behaviour and giving belove among.